Effects of p‐Type Nickel Oxide Semiconductor and Gold Bilayer on Highly Efficient Polymer Solar Cell. (26th September 2016) - Park, Jeong‐Woo; Shin, Sang‐Chul; Shim, Jae Won
Abstract : In this study, we report a new hole‐collecting interlayer (HCI) comprising NiO/Au/poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) for poly(3‐hexylthiophene) (P3HT) and phenyl‐C61‐butyric acid methyl ester (PCBM)‐based polymer solar cells (PSCs). The insertion of a bilayer of NiO/Au between indium tin oxide (ITO) and PEDOT:PSS improves the photocurrent generation of the PSCs. The NiO layer provides an intermediate step energy level between ITO and PEDOT:PSS, leading to enhanced hole collection. The ultrathin Au induces a surface plasmon resonance effect, allowing more photons to be absorbed by the photoactive layer and improving the hole‐collecting properties by planarizing and doping the NiO. The PSCs with the NiO/Au/PEDOT:PSS HCIs yield a power‐conversion efficiency of 3.9 ± 0.2%, which is approximately 15% higher than that of PSCs with a PEDOT:PSS‐only HCI, under a simulated air mass 1.5 global (G) 100 mW/cm 2 illumination. Abstract :